The effect of orifice depth and lip shape on the formation of a synthetic jet actuator - Siti Fatimatulzahara Abdul Jamil, 1995-, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Aeronautik)) - Universiti Teknologi Malaysia, 2019